Mobile Based Health Monitoring Application Development - Putri Syahfitri, Tiara; Yohana Br Ginting, Dewi; Jimmy, Jimmy Nganta Ginting; Kaban, Roberto (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
The Development of information technology has had a significant impact on health services, especially through the use of mobile-based health applications. Mobile applications offer easy access to information, improve communication between patients and medical personnel, and monitor health conditions in  real-time. This research aims to develop a mobile-based health monitoring application that can support health programs managed by the Binjai City Health Service. This application is designed to be able to monitor people’s health conditions periodically, remind people to carry out health checks, snd provide relevant health information. The waterfallmethod was chosen in developing this application because of its orderly structure, as well as the ease of access provided by the mobile platform. The application being developed is expected to be integrated with medical devices suchas heart monitors, body temperature and blood pressure sensors, to support the collection and analysis of real-time public health data. It is hoped that the results of this research will be an innovative solution for the Binjai City Health Service in improving public health services through mobile technology. REFERENCES     Azis, N., Pribadi, G., & Nurcahya, M. S, 2020, Analisa dan Perancangan Aplikasi Pembelajaran Bahasa Inggris Dasar Berbasis Android, Jurnal IKRA-ITH Informatika Vol 4 No 3 November 2020. Astuti, E. K., 2020, Peran BPJS Kesehatan Dalam Mewujudkan Hak Atas Pelayanan Kesehatan Bagi Warga Negara Indonesia, J-PeHI: Jurnal Penelitian Hukum Indonesia Volume 01, No. 01 Thn 2020. Ardiyanto, A., Ariman, & Supriyadi, E., 2021, Alat Pengukur Suhu Berbasis Arduino Menggunakan Sensor Inframerah Dan Alarm Pendeteksi Suhu Tubuh Diatas Normal, Program Studi Teknik Elektro - ISTN Sinusoida Vol. XXIII No. 1, Juli 2021 p-ISSN 1411 - 4593, e-ISSN 2722 – 0222. Ahdan, S., Susanto, E. R., & Syambas, N. R. (2019). Proposed Design and Modeling of Smart Energy Dashboard System by Implementing IoT (Internet of Things) Based on Mobile Device. 2019 IEEE 13th International Conference on Telecommunication Systems, Services, and Applications (TSSA), 194–199. Hendryani, A., 2020, Pengembangan Aplikasi Mobile Health Berbasis Android Untuk Monitoring Dan Evaluasi Stunting, Jurnal Sehat Mandiri, Volume 15 No 1 Juni 2020. Hendryani, A., 2020, Pengembangan Aplikasi Mobile Health Berbasis Android Untuk Monitoring Dan Evaluasi Stunting, Jurnal Sehat Mandiri, Volume 15 No 1Juni 2020. Kalam, M. N., Sianturi, R. S., & Kharisma, A. P., 2022, Perancangan User Experience Aplikasi Pemantauan Kesehatan Ibu Hamil di POLINDES berbasis Mobile menggunakan Metode Human Centered Design (HCD), Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer e-ISSN: 2548-964X Vol. 6, No. 7, Juli 2022, hlm. 3489-3498. Kusuma, Dedy Hidayat. “Si-Bidan: Sistem Informasi Kesehatan Ibu dan Anak”, INTENSIF, Vol.3 No.1 February 2019. Ambarwati and W. Wikusna, “Aplikasi Pelayanan Kesehatan Ibu dan Anak ( KIA ) di Puskesmas Cinunuk,” J. Teknol. Inf., vol. 2, no. 3, pp. 92–96, 2015. Annisa, “Pengembangan sistem informasi”Universitas Gadjah Mada, 2016 Maria, S., & Efendi, J, 2021, Perancangan Sistem Informasi Pelayanan Di Kantor Desa Ranah Baru Berbasis Web, Jurnal Intra Tech E-ISSN : 2549-0222 Vol 5, No.2, Oktober 2021 Nurahman, M. A., Sukowati, A. I., & Situmeang, A., 2021, Rancang Bangun Alat Pendeteksi Detak Jantung dan Saturasi Oksigen dalam Darah Berbasis Arduino MEGA 2560, Jurnal Ilmiah KOMPUTASI, Volume 20 No : 1, Maret 2021, p-ISSN 1412-9434/e-ISSN 2549-7227. Parjito, Rahmawati, O., & Ulum, F., 2022, Rancang Bangun Aplikasi E-Agribisnis Untuk Meningkatkan Penjualan Hasil Tanaman Hortikultura, Jurnal Informatika dan Rekayasa Perangkat Lunak (JATIKA) Vol. 3, No. 3, September 2022, 354-365. Permana, A. Y., & Romadlon, P., 2019, Perancangan Sistem Informasi Penjualan Perumahan Mengunakan Metode Sdlc Pada PT. Mandiri Land Prosperous Berbasis Mobile, SIGMA – Jurnal Teknologi Pelita Bangsa, Volume 10 Nomor 2 Desember 2019 ISSN : 2407-3903. Styawati, & Ariany, F., 2020, Sistem Monitoring Tumbuh Kembang Balita/Batita di Tengah Covid-19 Berbasis Mobile, Jurnal Informatika Universitas Pamulang ISSN: 2541-1004 Penerbit: Program Studi Teknik Informatika Universitas Pamulang e-ISSN: 2622-4615 Vol. 5, No. 4, Desember 2020 (490-497). Sany, F. A., & Arifin, A., 2023, Pengembangan Aplikasi Kesehatan: Systemic Literature Review, INFOTECH journal Vol (9) No (2) 2023, pp. 596-306. Alvionita, E. S. Manapa, M. Ahmad, W. Nontji, D. S. Riu and A. N. Usman, "Pengembangan Modul Deteksi Risiko Perdarahan Pada Kehamilan Efektif Meningkatkan Pengetahuan Ibu Hamil," Oksitosin: Jurnal Ilmiah Kebidanan, vol. 7, no. 2, pp. 134-148, 2020. S. Pongtambing and E. A. M. Sampetoding, "Transformasi Digital pada Layanan Kesehatan Berkelanjutan di Indonesia," SainsTech Innovation Journal, vol. 6, no. 2, pp. 412-420, 2023 S. Pongtambing, E. A. Sampetoding and E. S. Manapa, "Sistem Informasi Kesehatan Dan Telemedicine: Narrative Review," Compromise Journal: Community Proffesional Service Journal, vol. 4, no. 52-58, p. 1, 2023